EVALUASI PENGARUH BENTUK INTERAKSI PADA VIRTUAL REALITY TERHADAP PENURUNAN TINGKAT STRES MAHASISWA - Michelle Yut, Valencia
High mental workload on students can cause stress and lead to decreased motivation and impaired performance. Currently, universities intervene by providing counseling to students. However, ITB students find it difficult to get counseling schedules with a limited number of psychologists. One alternative that can be done to reduce stress independently is to see nature scenery. Virtual reality (VR) can offer nature exposure as an engaging and accessible alternative to the young population who use digital media more often than go outside. There are two forms of interaction in VR that can provide different experiences to its users. User experience can affect the user's response in reducing stress levels. Therefore, this study aims to evaluate the effect of the form of interaction in VR on reducing students’ stress levels. This research is conducted by providing a visual stimulus of natural scenery through a VR HMD device with two different forms of interaction. This study involved 18 participants. The experiment began with baseline measurements, giving stressors through several cognitive tests, and using VR both actively and passively. The parameters measured were subjective stress levels using the STAI-S questionnaire, objective stress levels using the HRV parameter, presence levels using the PQ questionnaire, immersion levels using the IEQ questionnaire, and cognitive performance using the average response time from doing the stroop task. The results showed that the use of VR with a visual stimulus of nature scenery can reduce students’ stress levels. Furthermore, the form of interaction in VR is proven to have an effect on reducing students’ stress levels, both subjectively and objectively. Active interaction in VR provides a greater reduction in the STAI-S score than passive interaction and produces a lower stress level compared to the initial conditions. Objectively, active interaction in VR also provides a higher stress reduction in the parameters of mean RR, mean HR, HF, and LF/HF ratio compared to passive interaction. Presence level immersion level, and the form of interaction in VR also significantly influenced the reduction of students’ stress levels.